Zoonotic tuberculosis : mycobacterium bovis and other pathogenic mycobacteria - Thoen, Charles O.; Steele, James H.; Kaneene, John B. (Wiley-Blackwell, 2014)
Zoonotic Tuberculosis: Mycobacterium bovis and Other Pathogenic Mycobacteria, Third Edition is a comprehensive review of the state of the art in the control and elimination of infections caused by Mycobacterium tuberculosis complex in animals and humans. This update to the most complete and current reference available on Mycobacterium bovis includes new coverage of the latest molecular techniques; more information on human infection and One Health; updates to the information on the International Union Against Tuberculosis and Lung Disease (IUATLD), the World Health Orga
Keywords: Tuberculosis